'Alzheimer-like' pathology in a murine model of arterial hypertension. (20th July 2011) - Carnevale, Daniela; Lembo, Giuseppe
Abstract : Genetic AD (Alzheimer's disease) accounts for only few AD cases and is almost exclusively associated with increased amyloid production in the brain. Instead, most patients are affected with the sporadic form of AD and typically have altered clearance mechanisms. The identification of factors that influence the onset and progression of sporadic AD is a key step towards understanding its mechanism(s) and developing successful therapies. An increasing number of epidemiological studies describe a strong association between AD and cardiovascular risk factors, particularly hypertension, that exerts detrimental effects on the cerebral circulation, favouring chronic brain hypoperfusion. However, a clear demonstration of a pathophysiological link between cardiovascular risk factors and AD aetiology is still missing. To increase our knowledge of the mechanisms involved in the brain's response to hypertension and their possible role in promoting amyloid deposition in the brain, we have performed and investigated in depth different murine models of hypertension, induced either pharmacologically or mechanically, leading in the long term to plaque formation in the brain parenchyma and around blood vessels. In the present paper, we review the major findings in this particular experimental setting that allow us to study the pathogenetic mechanisms of sporadic AD triggered by vascular risk factors.